Vampire rising - Henderson, Jason, 1971- (Henderson, Jason, 1971- Alex Van Helsing., 2010)
At a boarding school in Switzerland, fourteen-year-old Alex Van Helsing learns that vampires are real, that he has a natural ability to sense them, and that an agency called Polidorium ha been helping his family fight them since 1821.